2020
DOI: 10.3390/jimaging6110124
|View full text |Cite
|
Sign up to set email alerts
|

Boron-Based Neutron Scintillator Screens for Neutron Imaging

Abstract: In digital neutron imaging, the neutron scintillator screen is a limiting factor of spatial resolution and neutron capture efficiency and must be improved to enhance the capabilities of digital neutron imaging systems. Commonly used neutron scintillators are based on 6LiF and gadolinium oxysulfide neutron converters. This work explores boron-based neutron scintillators because 10B has a neutron absorption cross-section four times greater than 6Li, less energetic daughter products than Gd and 6Li, and lower γ-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Consequently, there are two common types of fast neutron imaging detectors: an integrated liquid or plastic scintillator which provides both high proton density and light emission, , or a two-part detector consisting of a hydrogen-dense matrix (often a plastic or polymer such as polypropylene (PP) or high-density polyethylene) and a scintillator material such as ZnS:Ag, ZnS:Cu, or Gd 2 O 2 S:Tb. The latter type has shown the most success to date, , with screens consisting of ZnS:Cu in a PP matrix, denoted hereafter as ZnS:Cu­(PP), showing a good combination of light output and spatial resolution that has led to their commercialization by RC Tritec AG. , However, long exposure times are still required to obtain high-quality images even under high fast neutron fluxes, while spatial resolution decreases substantially with thickness of the scintillator plate, likely due to light scattering at the phosphor–plastic interface, as the typical size of phosphor inclusions are larger than the emission wavelength. Another fundamental drawback is the afterglow of the ZnS:Cu phosphor, which exhibits a several minute decay under fast neutron beam exposure, problematic for the short repeated exposures required for computed tomography and precluding the use of such screens in pulsed neutron experiments with high repetition rates.…”
mentioning
confidence: 99%
“…Consequently, there are two common types of fast neutron imaging detectors: an integrated liquid or plastic scintillator which provides both high proton density and light emission, , or a two-part detector consisting of a hydrogen-dense matrix (often a plastic or polymer such as polypropylene (PP) or high-density polyethylene) and a scintillator material such as ZnS:Ag, ZnS:Cu, or Gd 2 O 2 S:Tb. The latter type has shown the most success to date, , with screens consisting of ZnS:Cu in a PP matrix, denoted hereafter as ZnS:Cu­(PP), showing a good combination of light output and spatial resolution that has led to their commercialization by RC Tritec AG. , However, long exposure times are still required to obtain high-quality images even under high fast neutron fluxes, while spatial resolution decreases substantially with thickness of the scintillator plate, likely due to light scattering at the phosphor–plastic interface, as the typical size of phosphor inclusions are larger than the emission wavelength. Another fundamental drawback is the afterglow of the ZnS:Cu phosphor, which exhibits a several minute decay under fast neutron beam exposure, problematic for the short repeated exposures required for computed tomography and precluding the use of such screens in pulsed neutron experiments with high repetition rates.…”
mentioning
confidence: 99%
“…11 As Tl 3 Cl[B 12 H 12 ] also shows strong blue radioluminescence peaking at 445 nm upon 50 keV excitation (Fig. 14) and has a fairly high density ( ρ = 4.06 g cm −3 ), this novel 6s 2 -cation hydroborate can be regarded as a promising molecular scintillator, which deserves further investigation for application in high-energy physics, neutron detectors, 35 or medical imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Dalton Transactions be regarded as a promising molecular scintillator, which deserves further investigation for application in high-energy physics, neutron detectors, 35 or medical imaging.…”
Section: Papermentioning
confidence: 99%
“…However, earlier reports about trial screens containing boron showed much lower light output than expected, to an extent that made those screens practically unusable. Simulations performed in [4] showed the range of the reaction products to be on the order of only 2-3 µm in any boron-containing substance, as shown in Table 1.…”
Section: Boron-based Screensmentioning
confidence: 99%
“…However, due to the low energy of the main conversion electrons from neutron capture in 157 Gd (29 keV + 71 keV), the range of the reaction products in Gadox is very low, on the order of a few micrometers. Also the light yield from the smaller deposition energy is much less than that of 6 LiF in zinc sulfide, only 3.29 photons per neutron capture on average [4]. Due to the much higher cross section of Gd and thus much higher detection efficiency, screens can be thinned to 10-20 µm for nearly full absorption, delivering a resolution about equal to the range of the thickness.…”
Section: Introductionmentioning
confidence: 99%